PELATIHAN GERAKAN PADA KONDISI ANAEROBIC DAPAT MENINGKATKAN WAKTU TEMPUH RENANG DADA 100 METER EKSTRAKURIKULER SISWA SMK NEGERI 2 KOTA KUPANG NUSA TENGGARA TIMUR - Maria Imaculata Date; Luh Made Indah Sri Handari Adiputra; I Putu Adiartha Griadhi; Susy Purnawati; I Made Muliarta; I Made Krisna Dinata (Sport and Fitness Journal, 2019)
Swimming with anaerobic conditions in a short distance in the fastest traveling time that is needed to determine the performance students. The results of good performance are the provision of meaningful load on repetition, and the speed of motion measured measuring the distance traveling time certain distance. Reveal that movement training in anaerobic conditions can increase the travel time of breaststroke swimming 100 meters extracurricular students of State Vocational High School 2 Kupang City, East Nusa Tenggara.This study used an eksperimental randomized pretest-posttest control group design involving 26 extracurricular swimming students, aged 15-19 years, height, and weight, with a normal body mass index (BMI) with an average of 19.15 ± 0.36 kg / m². The research subjects were divided into two groups, namely the treatment group swimming training in anaerobic conditions 8 x 25 meters repetition, 4 repetitions, 5 sets, 3 times a week for 6 weeks, while the control group anaerobic swimming training 4 x 50 meters repetition, 3 reps, 5 sets, 3 times a week for 6 weeks. Showed that the average trevel time treatment group was swimming training 135.85±4.85 seconds, while in the control group was 134.77 ± 4.23 seconds, t=0.604 and the value of p=0.552. While after treatment, average trevel time the treatment group was 114.23 ± 5.22 seconds, while in the control group it was swimming training 126.08 ± 5.07 seconds t=-5.870 and p value <0.001. Travel times for swimming students were significantly different (p<0.05) between the two groups, movement Training in Anaerobic Conditions can increase travel time for 100-Meter breaststroke swimming style extracurricular Students of State Vocational High School 2 Kupang City, East Nusa Tenggara.Keywords: Anaerobic , traveling time, 100 meter breaststroke pool.